A green and efficient approach to selective conversion of xylose and biomass hemicellulose into furfural in aqueous media using high-pressure CO2 as a sustainable catalyst. Issue 10 (10th March 2016) - Morais, Ana Rita C.; Matuchaki, Maria Daniela D. J.; Andreaus, Jürgen; Bogel-Lukasik, Rafal
Abstract : A novel approach to produce furfural from lignocellulosic biomass with green solvents without the use of mineral acids or heterogeneous catalysts. Abstract : This work introduces a novel approach to produce furfural from lignocellulosic biomass without the use of mineral acids or heterogeneous catalysts. The proposed concept consists of two reaction stages. The first one consists of an extraction of hemicellulose from wheat straw using high-pressure CO2 and H2 O to produce a water-soluble fraction containing pentoses in oligomeric and monomeric forms. The second step involves the conversion of this fraction into furfural in a system consisting of water, tetrahydrofuran (THF), methyl isobutyl ketone (MIBK) and high-pressure CO2 at elevated temperatures with MIBK as the water immiscible extracting solvent. At 200 °C and 50 bar of initial CO2 pressure, the high-pressure CO2 and H2 O assisted process of hemicellulose extraction resulted in 81 mol% conversion of hemicellulose into xylose and arabinose (mainly as oligomers). Prior to the use of the produced hemicellulose hydrolysate in dehydration reactions to obtain furfural, a series of preliminary trials with xylose, as a model compound, were performed. The biphasic system with water/THF/MIBK under the reaction conditions with 50 bar of initial CO2 pressure, at 180 °C, 60 min favoured the production of furfural and allowed to obtain furfural at a yield and selectivity of 56.6 mol% and 62.3 mol%, respectively. Under the same conditions, hemicellulose hydrolysate dehydration yielded 43 mol% of furfural with a selectivity of 44 mol%.